Content-Based and Task-Based Language Teaching in L2 Classroom - Amat, Eleonor; Tejada, John Karl; Ilustre, Ramil (Journal of English Language Teaching and Applied Linguistics, 2022)
This recent journal offered a brief review of significant research findings on second language acquisition related to two language approaches, namely, Content-Based Language Teaching (CBLT) and Task-Based Language Teaching (TBLT). Based on different research provided in this journal, the following strengthen the role, effectiveness, and importance of CBLT and TBLT in a language classroom by improving language instructions and learning processes during the acquisition of a second language.